Ethical and Socially Responsible Behaviour of Tax Advisers: The Case of Moral Beliefs - Prauliņš, Artūrs; Bratka, Valda (Socialiniai tyrimai, 2014)
Financial crisis and corporate scandals have turned the spotlight on the role played by tax advisors in the creation and development of tax minimization schemes. This paper explores whether society is entitled to expect tax advisors to behave in an ethical and socially responsible manner and to have general moral obligations. A modern contradictory role of tax advisors has been analyzed, influencing a predatory entrepreneurial culture, and the conflicting mental attitude of society and clients have been investigated. The study concludes that significant differences in tax advisors’ ethical sensitivity and personal moral beliefs have been insurmountable obstacles to meeting these expectations thus far.